Analysis of Individual Aspects in Riverbank Slums on Sustainable Sanitation Development (Case Study: Bima City, NTB, Indonesia) - Gusmiati, Gusmiati; Soewondo, Prayatni; Awfa, Dion; Halomoan, Nico; Sarli, Prasanti Widyasih; Setiyawan, Ahmad Soleh (Journal of Engineering and Technological Sciences, 2024)
Currently, 24.5% of the population of Bima City lack access to sanitation. The issue is predominantly concentrated in densely populated urban slums along the riverbanks, influenced by the cultural and societal context of Indonesian society. From 2021 to 2022, a comprehensive mixed-method study was conducted in three urban slums, applying the Integrated Framework for Sanitation Services (IFSS) to explore individual aspects within a socio-cultural context. Combining quantitative and qualitative methods, the research involved a household questionnaire survey and in-depth interviews (IDI). The study revealed that individual aspects are shaped by perceptions of the convenience of open defecation and latrine use as well as experiences with shared latrines, driving the adoption of private latrines. Challenges such as financial constraints and limited construction capabilities in urban slum communities often hinder latrine construction, though cultural and traditional values (adat) in the Bima community in urban slums help to alleviate these obstacles. A recommendation is made to enhance the monitoring of sanitation adoption progress, focusing on the sanitation system’s functioning and adherence to the sanitation hierarchy. Despite awareness of the importance of safe disposal, its impact on sanitation behavior in Bima City’s urban slums has been constrained, underscoring the imperative for effective behavior change communication strategies.